NOMA COOPERATIVE RELAYING SYSTEMS OVER RICIAN-SHADOWED FADING CHANNELS - Panić, Stefan R.; Khotnenok, Sergei (Bulletin of Natural Sciences Research, 2022)
Non-orthogonal multiple Access (NOMA) is an efficient 5G technology that enables network spectral efficiency increase and network access latency. In order to additionally improve the reliability of transmission and increase the achievable rate of NOMA system, combined utilization of NOMA and cooperative relay transmission (CRS) could appear as effective remedy. In this work, we will carry out performance analysis of NOMA based CRS over Rician-Shadowed fading channels. The closed-form expression for the exact average achievable rate is presented in the form of Meijer G functions infinite-series. Numerical results are presented in order to manifest the credibility of the presented method.